SYSTEMIC ENTREPRENEURSHIP INTENTION MODEL, FAMILY BACKGROUND, AND PRIOR ENTREPRENEURIAL EXPERIENCE ON STUDENTS' ENTREPRENEURIAL INTENTION - Suhermin, Suhermin; Suryawirawan, Okto Aditya; Bon, Abdul Talib (Universitas Brawijaya, Indonesia, 2023)
Countless businesses had to close permanently, and workers had to be laid off during Covid-19 pandemic, thus the emergence of entrepreneurs is crucial for Indonesia's economic recovery. This study aims to analyze further the extended systemic entrepreneurship intention model and its impact on students in Surabaya. Purposive sampling was used toward 205 students. Results were analyzed using partial least square through SmartPLS. Reciprocal relationships among all the antecedent variables of entrepreneurial intention were found to be positive and significant. Regarding the impact of the antecedent variables of entrepreneurial intention such as perceived convenience, risk tolerance, perceived feasibility and attitude, only perceived feasibility was found to have no effect on entrepreneurial intention. There are no differences in entrepreneurial intention among students with or without entrepreneurial family backgrounds. There are no differences in entrepreneurial intention among students with or without prior entrepreneurial experience. This study provides implication towards students' entrepreneurial intention during covid-19 pandemic and the robustness of systemic entrepreneurship intention model in predicting it.